Mechanical and structural performance of hardwood charcoal-reinforced polyester composites: Effects of particle size and filler loading - Francis O. Edoziuno; Benjamin U. Odoni; Cynthia C. Nwaeju; M. Saravana Kumar; Alaa F. Abd El-Rehim (Results in Engineering)
This study investigates the development and characterization of hardwood charcoal-reinforced polyester composites prepared with varying particle sizes (75, 150, 250, and 300 µm) and filler loadings (5–30 wt. %). Hardwood charcoal was milled, sieved, and incorporated into a polyester matrix. Water absorption tests revealed minimal uptake across most composites due to strong filler-matrix bonding and the hydrophobic nature of polyester, with slight increases observed at specific particle sizes and low loadings, attributed to microvoids or weak adhesion. XRD analysis showed a crystallinity index of 75.53 % for the composites, reflecting the contribution of the hardwood charcoal filler (79 % crystallinity) compared to 50.17 % for the unreinforced polyester. SEM-EDS imaging confirmed minimal particle agglomeration. Tensile tests revealed optimal filler loadings for each particle size that maximize UTS, with peaks observed at 10 wt. % (11.43 MPa), 20 wt. % (11.898 MPa), 5 wt. % (12.31 MPa), and 20 wt. % (18.028 MPa) for 75 µm, 150 µm, 250 µm, and 300 µm fillers, respectively. Flexural strength improved with smaller fillers at low loadings (5–10 wt. %) due to uniform stress distribution, while larger fillers and high loadings reduced performance due to voids and weaker adhesion. Optimized filler size and loading effectively enhance the mechanical properties of hardwood charcoal-reinforced polyester composites.